(untitled) (Global Journals of Research in Engineering, 2023)
The performance of chip is degraded because of the short-channel effect SCE as the metal oxide semiconductor field effect transistor MOSFET size scales down Silicon on insulator SOI technology helps to reduce the short channel effects and permits a good solution to the miniaturization The electrical characteristics of fully depleted SOI FDSOI and partially depleted SOI PDSOI n-channel MOSFET N-MOSFET are investigated as silicon film thickness is varied in this paper Both transistors are compared in terms of electrical parameters which are the threshold voltage subthreshold slope on-state current leakage current and drain induced barrier lowering DIBL Silvaco TCAD tools are used for simulating both PDSOI and FDSOI MOSFETs FDSOI MOSFET is superior to PDSOI MOSFET based on found simulation results